Erythrofordins D and E, two new cassaine-type diterpenes from Erythrophleum suaveolens. Issue 2 (15th January 2019) - Grkovic, Tanja; Evans, Jason R.; Akee, Rhone K.; Guo, Liang; Davis, Myrtle; Jato, Johnson; Grothaus, Paul G.; Ahalt-Gottholm, Michelle; Hollingshead, Melinda; Collins, Jerry M.; Newman, David J.; O'Keefe, Barry R.
Graphical abstract: Abstract: Two new cassaine-type diterpenoids, namely erythrofordins D (1 ) and E (2 ), sourced from a Cameroon collection of Erythrophleum suaveolens were isolated and assessed for anti-tumor activity. In the NCI-60 cancer cell assay, erythrofordins D (1 ) and E (2 ) were found to be cytotoxic in the low micro molar ranges with a mean GI50 value of 2.45 and 0.71 µM, mean TGI value of 9.77 and 2.29 µM, and a mean LC50 of 26.92 and 11.48 µM for1 and2 respectively. Using the COMPARE algorithm, the new compounds were found to have similar NCI-60 response profiles to the known cardiac glycosides hyrcanoside and strophanthin. In addition, in an assay examining the viability and contractile function in human cardiomyocytes derived from induced pluripotent stem-cells, erythrofordins showed cardiotoxicity effects at concentrations as low as 0.03 µg/mL.